Pengaruh Budaya Organisasi Kompensasi dan Motivasi Berprestasi Terhadap Kinerja Dosen Tetap Serta Dampaknya Pada Mutu Pendidikan Universitas Abulyatama Aceh - Lukman T Ibrahim; Mukhlis Yunus; Amri Amri (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
This study aims to determine the influence of organizational culture of compensation and achievement motivation on the performance of tenured faculty as well as the impact on the quality of university education Abulyatama Aceh. The study used the SEM analysis model AMOS. After processing the data, obtained by the results of studies showing that the Cultural Organization (X1) Compensation (X2) Achievement Motivation (X3), Performance (Y) and Quality of Education (Z) positively and significantly affect the quality of education at the University Abulyatama Aceh. Thus the hypothesis is entirely acceptable, which means that ( a) the organizational culture in a positive and significant effect on the performance of full-time lecturer at the University Abulyatama Aceh is tested were correct; (b) compensation and significant positive effect on the performance of full-time lecturer at the University Abulyatama Aceh is verified; (c) achievement motivation in a positive and significant effect on the performance of full-time lecturer at the University Abulyatama Aceh is verified; (d) performance and significant positive effect on the quality of education at the University Abulyatama Aceh is verified; (e) the organization's culture, compensation, achievement motivation together in a positive and significant effect on the performance of faculty and the quality of education at the University Abulyatama Aceh